Transforming Freelance Designers in the Digital Creative Economy through AI Visual Prompting - Haesal Haesal; Btari Mariska Purwaamijaya; Muhammad Dzikri Ar Ridlo (Dinasti International Journal of Education Management and Social Science, 2025)
The rapid advancement of generative artificial intelligence (AI) tools such as Midjourney, DALL·E, and Stable Diffusion has fundamentally transformed the creative industry, particularly the freelance design sector. This study aims to explore how Indonesian freelance designers reinterpret their professional identity amid AI integration. Using a qualitative phenomenological design through Interpretative Phenomenological Analysis (IPA) combined with Critical Discourse Analysis (CDA), the research involved six freelance designers who actively use AI visual prompt tools in their work. The findings reveal a paradoxical dynamic: AI serves as an efficiency catalyst while simultaneously generating emotional and professional tension. Designers respond to this disruption through three strategies; embracing AI as a collaborative accelerator, reaffirming the irreplaceable value of human creativity, and adopting adaptive economic strategies to maintain relevance in the gig economy. The study concludes that AI does not replace designers but repositions them as strategic mediators who combine technical literacy, critical reflection, and artistic intuition. These insights contribute to design research by illuminating how creative professionals renegotiate value and authorship in the digital creative economy.